Mentalization mediates the relationship between borderline personality features and internalizing and externalizing psychopathology in adolescents - Norup, Ditte Aagaard (Scand J Child Adolesc Psychiatr Psychol, 2019)
BACKGROUND: Findings show that deficiencies in the ability to understand mental states are related to many forms of psychopathology. Mentalizing dysfunctions are suggested to be the core pathology underlying borderline personality disorder (BPD). Moreover, research suggests that BPD predicts psychopathology in general and findings display that diminished mentalization is related to a range of psychiatric disorders. As yet, no study has investigated the potential link between borderline personality features, mentalization and internalizing and externalizing psychopathology, and whether internalizing and externalizing psychopathology in BPD might be driven by impaired mentalization. OBJECTIVE: In a cross-sectional study, 109 patients referred to a child and adolescent psychiatric clinic were assessed with a battery of self-report instruments to asses borderline personality features, mentalization, and internalizing and externalizing psychopathology. METHOD: Simple mediation model was used to examine whether mentalizing abilities mediated the relationship between borderline features and psychopathology in regard to externalizing and internalizing psychopathology in adolescents. RESULTS: The results indicated that mentalization mediated the relationship between borderline personality features and both externalizing and internalizing psychopathology in adolescents, indicating that mentalization underlie externalizing and internalizing psychopathology in adolescents with borderline personality features. CONCLUSION: The current study is the first empirical study to evaluate mentalization as a mediating factor between adolescents who met full or sub-threshold criteria for BPD and psychopathology. Clinical implications are discussed.